2019
DOI: 10.2478/fon-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Development of an assessment and intervention protocol for postpartum hemorrhage in the mainland of China: an evidence-based method and Delphi consult

Abstract: Objective Postpartum hemorrhage (PPH) is a leading cause of maternal death. Although guidelines have been updated, those with detailed protocols are limited for nursing practice. This study aims at establishing an early assessment and intervention protocol as a toolkit for PPH for midwives and obstetrical nurses. Methods Employing the evidence-based method, a systematic Internet search of guidelines was conducted and appraisal of literatures was conducted with AGREE system and Oxman-Guyatt Overview Quality As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Liu et al conducted an ultrasound image scanning study on the active part of the uterine contraction of Leonurus injection and found that the active parts of the excitement uterus are B1 (mainly hydrazine), B2 (mainly hydrazine, fenugreek), and B4 (mainly contains fenugreek, choline, and total amino acids), and the part of the diastolic uterus is B3 (mainly containing fenugreek and choline). The study found that no matter if motherwort injection is used alone or combined with oxytocin, both can effectively prevent and treat postpartum hemorrhage during normal delivery and uterine delivery [ 10 ]. Yu Changli and others used motherwort injection combined with oxytocin after delivery of the fetus's anterior shoulder, immediately intramuscular injection into the hip to prevent and treat postpartum hemorrhage after delivery; the results show that the combination of drugs is significantly better than the single use because the onset of oxytocin is fast, but its half-life is short (3-4 min), and the maintenance time is short, and motherwort injection has a slower onset, but has a long-lasting uterine contraction and hemostasis effect; the combined effect is complementary, the hemostatic effect is obvious, and it has the function of promoting uterine involution [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al conducted an ultrasound image scanning study on the active part of the uterine contraction of Leonurus injection and found that the active parts of the excitement uterus are B1 (mainly hydrazine), B2 (mainly hydrazine, fenugreek), and B4 (mainly contains fenugreek, choline, and total amino acids), and the part of the diastolic uterus is B3 (mainly containing fenugreek and choline). The study found that no matter if motherwort injection is used alone or combined with oxytocin, both can effectively prevent and treat postpartum hemorrhage during normal delivery and uterine delivery [ 10 ]. Yu Changli and others used motherwort injection combined with oxytocin after delivery of the fetus's anterior shoulder, immediately intramuscular injection into the hip to prevent and treat postpartum hemorrhage after delivery; the results show that the combination of drugs is significantly better than the single use because the onset of oxytocin is fast, but its half-life is short (3-4 min), and the maintenance time is short, and motherwort injection has a slower onset, but has a long-lasting uterine contraction and hemostasis effect; the combined effect is complementary, the hemostatic effect is obvious, and it has the function of promoting uterine involution [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%